Positive pole piece, preparation method of positive pole material, battery and energy storage device

By designing radial and arc-shaped hole structures in lithium manganese iron phosphate positive electrode material, the problems of insufficient conductivity and Li+ diffusion coefficient are solved, and higher capacity and rate performance are achieved, broadening the application prospects of secondary batteries in energy storage applications.

CN119542356APending Publication Date: 2025-02-28XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693963.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The conductivity and Li+ diffusion coefficient of lithium manganese iron phosphate cathode material are poor, which makes it difficult to fully utilize its capacity and rate performance, limiting the application prospects of secondary batteries in energy storage applications.

Method used

A positive electrode material with the LiMnxFe1-x-yMyPO4 chemical formula is used, and the particle cross-section has a first hole and a second hole in an arc shape. By regulating the area and length of the second hole, the wetting property of the electrolyte and the migration path of Li+ are optimized.

Benefits of technology

It improves the capacity and rate performance of the cathode material, enhances the cycle stability of the secondary battery and the prospect of energy storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542356A_ABST
    Figure CN119542356A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece, a preparation method of a positive pole material, a battery and an energy storage device, the positive pole piece comprises a positive pole current collector, at least one surface of the positive pole current collector is provided with a positive pole material layer, the positive pole material layer comprises a positive pole material, the positive pole material has a chemical formula LiMnxFe1-x-yMyPO4, x is more than or equal to 0.5 and less than or equal to 0.7, y is more than or equal to 0.01 and less than or equal to 0.04, and an M element is selected from at least one of Mg or Ti; the cross section of the particle of the positive electrode material is provided with first holes which are radially distributed, and the central area of the cross section is also provided with arc-shaped second holes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a positive electrode sheet, a method for preparing a positive electrode material, a battery and an energy storage device. Background Art

[0002] Secondary batteries (such as lithium-ion batteries) have the characteristics of high specific energy, high operating voltage, low self-discharge rate, small size and light weight. They are widely used in various fields such as energy storage, portable electronic devices and electric vehicles.

[0003] Lithium manganese iron phosphate has relatively good safety and cycle performance. However, the conductivity of lithium manganese iron phosphate, Li + The diffusion coefficient is worse than that of lithium iron phosphate, which makes it difficult to fully exert the capacity performance of the positive electrode material. Moreover, due to its large impedance, under constant power test conditions, the discharge capacity of the positive electrode material is further reduced, which limits the use of lithium manganese iron phosphate in energy storage applications and affects the battery's rate performance and cycle performance. Summary of the invention

[0004] In order to solve the above technical problems, the present application discloses a positive electrode sheet, a method for preparing a positive electrode material, a battery and an energy storage device to improve the rate performance and cycle performance of secondary batteries, thereby broadening the application prospects of secondary batteries based on lithium iron manganese phosphate in energy storage application scenarios.

[0005] In a first aspect, the present application provides a positive electrode sheet, comprising a positive electrode current collector, at least one side of the positive electrode current collector having a positive electrode material layer, the positive electrode material layer comprising a positive electrode material, wherein:

[0006] The positive electrode material has the chemical formula LiMn x Fe 1-x-y M y PO4, 0.5≤x≤0.7, 0.01≤y≤0.04, M element is selected from at least one of Mg and Ti;

[0007] The cross section of the particles of the positive electrode material has radially distributed first holes, and the central area of ​​the cross section also has arc-shaped second holes.

[0008] In some embodiments of the present application, in the cross section of the positive electrode material particle, the area of ​​the second pore accounts for A in the total area of ​​the cross section, and 8%≤A≤21%.

[0009] In some embodiments of the present application, the length of the second hole is L, and L≥5 μm.

[0010] In some embodiments of the present application, the cross section of the particle of the positive electrode material has a plurality of radial ion transmission channels, and each of the ion transmission channels is formed by a plurality of the first holes distributed along the center to the surface of the cross section.

[0011] In some embodiments of the present application, the Dv50 of the positive electrode material is 5 μm to 8 μm.

[0012] In some embodiments of the present application, the XRD spectrum of the positive electrode material includes a first diffraction characteristic peak (110) and a second diffraction characteristic peak (131), and the peak intensity of the first diffraction characteristic peak is I 110 , the peak intensity of the second diffraction characteristic peak is I 131 , 1.445≤I 131 / I 110 ≤1.455.

[0013] In some embodiments of the present application, the button cell containing the positive electrode plate has a 0.5C discharge capacity of not less than 140 mAh / g, a 1C discharge capacity of not less than 130 mAh / g, and a 200-cycle capacity retention rate of not less than 84%.

[0014] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0015] According to LiMn x Fe 1-x-y M y Iron source, manganese source, phosphorus source, lithium source and M element source are weighed as reaction raw materials in the stoichiometric ratio required by PO4, and water is added and mixed to prepare a metal salt solution, wherein 0.5≤x≤0.7, 0.01≤y≤0.04, and M element is selected from at least one of Mg and Ti;

[0016] After mixing the metal salt solution, the porous hollow carbon microspheres, the precipitant solution and the complexing agent solution, the pH value of the reaction system is maintained to be greater than or equal to 10, and a precipitation reaction is performed to obtain a lithium manganese iron phosphate precursor;

[0017] The obtained lithium manganese iron phosphate precursor is mixed with a carbon source and then spray-dried to form a powder;

[0018] The obtained powder is subjected to a high temperature sintering treatment at a temperature of 650° C. to 750° C. to obtain a positive electrode material.

[0019] In some embodiments of the present application, the mass ratio of the porous hollow carbon microspheres to the reaction raw materials is (10-15):100.

[0020] In some embodiments of the present application, the mass ratio of the lithium manganese iron phosphate precursor to the carbon source is (93-97): (3-7).

[0021] In some embodiments of the present application, the porous hollow carbon microspheres are obtained by the following steps:

[0022] The sucrose solution is spray-dried to form a carbon microsphere precursor;

[0023] The carbon microsphere precursor is subjected to a low-temperature sintering treatment at a temperature of 400° C. to 450° C. to obtain the porous hollow carbon microsphere.

[0024] In a third aspect, the present application provides a battery, comprising the positive electrode plate described in the first aspect.

[0025] In a fourth aspect, the present application provides an energy storage device, comprising a housing and at least one battery as described in the third aspect, wherein the battery is accommodated in the housing.

[0026] In a fifth aspect, the present application provides an electrical device, comprising the energy storage device described in the fourth aspect, wherein the energy storage device supplies power to the electrical device.

[0027] Compared with the prior art, this application has at least the following beneficial effects:

[0028] The present application provides a positive electrode sheet, a method for preparing a positive electrode material, a battery and an energy storage device, wherein the positive electrode material in the positive electrode sheet has a chemical formula of LiMn x Fe 1-x-y M y PO4, 0.5≤x≤0.7, 0.01≤y≤0.04, M element is selected from at least one of Mg or Ti, and is a lithium manganese iron phosphate positive electrode material; the cross section of the positive electrode material has radially distributed first holes, and the central area of ​​the cross section also has arc-shaped second holes. The structural distribution characteristics of the first holes and the second holes are conducive to the efficient and rapid infiltration of the electrolyte into the particles of the positive electrode material, and shortening the Li + The migration distance of the positive electrode material can be increased, thereby improving the capacity performance and rate performance of the positive electrode material. When the positive electrode sheet with the positive electrode material of the present application is used in a secondary battery, the rate performance and cycle performance of the secondary battery can be improved. When the above-mentioned secondary battery is used in an energy storage device, it can broaden the application prospects of secondary batteries based on lithium manganese iron phosphate positive electrode materials in energy storage application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 A scanning electron microscope (SEM) image of a cross section of a positive electrode material in one embodiment of the present application;

[0031] Figure 2 A schematic diagram of the structure of particles of a positive electrode material in one embodiment of the present application;

[0032] Figure 3 A schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application;

[0033] Figure 4 A schematic diagram of the structure of an energy storage system according to an implementation scheme of the present application;

[0034] Figure 5 The X-ray diffraction (XRD) spectrum of the positive electrode material in one embodiment of the present application.

[0035] Explanation of the accompanying drawings: 1-energy storage device, 2-electric energy conversion device, 3-first user load, 4-second user load, 10-first hole, 20-second hole, 30-ion transmission channel, 400-energy storage system, 410-high voltage cable, 420-first electric energy conversion device, 430-second electric energy conversion device. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0037] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.

[0038] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.

[0039] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0040] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0041] It should be noted that, in the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0042] The inventors found that in the related art, although there are holes in the particles of lithium manganese iron phosphate positive electrode materials, the holes are tortuous and even partially form ring-shaped closed holes, the so-called "dead holes". + The longer diffusion path is not conducive to the capacity of lithium manganese iron phosphate positive electrode materials and affects the electrochemical performance of lithium-ion batteries.

[0043] In view of this, the present application provides a positive electrode plate, the positive electrode plate includes a positive electrode current collector, at least one side of the positive electrode current collector has a positive electrode material layer, the positive electrode material layer includes a positive electrode material, wherein the positive electrode material has a chemical formula of LiMn x Fe 1-x-y M y PO4, 0.5≤x≤0.7, 0.01≤y≤0.04, for example, x is 0.5, 0.6 or 0.7; y is 0.01, 0.02 or 0.04, and the M element is selected from at least one of Mg and Ti. Figure 1 and Figure 2 The cross section of the positive electrode material particle has radially distributed first holes 10; the central area of ​​the cross section also has arc-shaped second holes 20. In this way, during the lithium-ion battery cycle, the external electrolyte first enters the positive electrode material particle through the radially distributed first holes, and then further enters the central part of the positive electrode material particle through the arc-shaped second holes. Through the combined effect of the first holes and the second holes, the electrolyte is efficiently and quickly infiltrated into the positive electrode material particle; and during the lithium-ion battery cycle, the radially distributed first holes are conducive to Li +The arc-shaped second hole reduces the tortuosity of the internal hole path, which is conducive to shortening the Li + The diffusion path of Li + When the positive electrode sheet with the positive electrode material of the present application is applied to a lithium-ion battery, the rate performance and cycle performance of the lithium-ion battery can be improved, and the application prospects of lithium-ion batteries based on lithium iron manganese phosphate positive electrode materials in energy storage applications can also be broadened.

[0044] In an optional embodiment, in the cross section of the particles of the positive electrode material, in the cross section of the particles of the positive electrode material, the area of ​​the second hole accounts for A in the total area of ​​the cross section, 8%≤A≤21%, for example, A is 8%, 10%, 15%, 18% or 21%. When A is too small (for example, less than 8%), it indicates that the second hole is too small, the wettability to the electrolyte becomes poor, which is not conducive to the performance of the capacity performance of the positive electrode material, and thus is not conducive to the performance of the capacity performance of the lithium-ion battery; when A is too large (for example, greater than 21%), it indicates that the second hole is too large. Although the wettability to the electrolyte is good, the overall mechanical strength of the particles of the positive electrode material is low, and the positive electrode material is prone to breakage during the cycle process, which is not conducive to the improvement of the cycle performance of the lithium-ion battery. By regulating the value of A within the above range, the positive electrode material particles can have good electrolyte wettability and sufficient mechanical strength, which is conducive to the improvement of the capacity performance and cycle performance of the lithium-ion battery.

[0045] In an optional embodiment, the length of the second pore is L, L ≥ 5 μm, preferably 5 μm ≤ L ≤ 15 μm. For example, L is 5 μm, 10 μm or 15 μm. In this way, it is beneficial to form a second pore with sufficient length inside the positive electrode material particles, so that the electrolyte can more fully infiltrate the inside of the positive electrode material particles through the second pores.

[0046] In an alternative embodiment, see Figure 1 and Figure 2 The cross section of the positive electrode material particle has a plurality of radial ion transmission channels 30, and each ion transmission channel 30 is formed by a plurality of first holes 10 distributed along the center to the surface of the cross section. Figure 2 The dashed arrows in the figure show that during the lithium-ion battery cycle, Li + The ion transport channel 30 can be used to migrate, and the ion transport channel 30 presents a linear path from the center of the positive electrode material particles to the surface, so that Li + More inclined to migrate along a straight line, shortening Li + migration distance.

[0047] In an optional embodiment, the Dv50 of the positive electrode material is 5 μm to 8 μm. For example, the Dv50 of the positive electrode material is 5 μm, 6 μm, 7 μm or 8 μm. In this way, the positive electrode material has a higher compaction density and the capacity performance is fully utilized, which is beneficial to improve the capacity performance and cycle performance of the lithium-ion battery.

[0048] In the present application, Dv50 means a particle size at which the volume accumulation is 50% from the smaller particle size side in a volume-based particle size distribution of particles.

[0049] In an optional embodiment, the XRD spectrum of the positive electrode material includes a first diffraction characteristic peak (110) and a second diffraction characteristic peak (131), and the peak intensity of the first diffraction characteristic peak is I 110 , the peak intensity of the second diffraction characteristic peak is I 131 , 1.445≤I 131 / I 110 ≤1.455, showing a typical lithium manganese iron phosphate crystal phase.

[0050] In an optional embodiment, the button cell containing the positive electrode plate has a 0.5C discharge capacity of not less than 140 mAh / g, a 1C discharge capacity of not less than 130 mAh / g, and a 200-cycle capacity retention rate of not less than 84%. It has a high discharge capacity and good cycle performance, which is beneficial to improving the comprehensive performance of lithium-ion batteries.

[0051] The present application also provides a method for preparing a positive electrode material, comprising the following steps:

[0052] Step A: According to LiMn x Fe 1-x-y M y An iron source, a manganese source, a phosphorus source, a lithium source and an M element source are weighed as reaction raw materials in the stoichiometric ratio required by PO4, and water is added and mixed to form a metal salt solution, wherein 0.5≤x≤0.7, 0.01≤y≤0.04, and the M element is selected from at least one of Mg and Ti;

[0053] Step B, after mixing the metal salt solution, the porous hollow carbon microspheres, the precipitant solution and the complexing agent solution, maintaining the pH value of the reaction system to be greater than or equal to 10, and performing a precipitation reaction to obtain a lithium manganese iron phosphate precursor;

[0054] Step C, mixing the obtained lithium manganese iron phosphate precursor with a carbon source and spray drying the mixture to form a powder;

[0055] Step D: subjecting the obtained powder to a high temperature sintering treatment at a temperature of 650° C. to 750° C. to obtain a positive electrode material.

[0056] In step A, the iron source can be selected from ferrous oxalate, ferrous sulfate or ferric chloride, the manganese source can be selected from manganese dioxide or manganese sulfate, the phosphorus source can be selected from phosphoric acid or ammonium dihydrogen phosphate, and the lithium source can be selected from lithium carbonate or lithium hydroxide; when the M element source is a Mg element source, the Mg element source can be magnesium oxide; when the M element source is a Ti element source, the titanium element source can be selected from titanium tetrachloride or titanium oxalate. In the metal salt solution, the total mass fraction of the reaction raw materials is 85% to 95%, which is not particularly limited in this application and can be adjusted by technicians according to actual conditions.

[0057] In step B, the precipitant solution can be a sodium hydroxide solution with a concentration of 0.5 mol / L to 1.5 mol / L; the complexing agent solution can be an ammonia solution with a concentration of 0.5 mol / L to 1.5 mol / L; the reaction temperature of the precipitation reaction is 140°C to 160°C, and the reaction time is 10h to 15h. After the reaction is completed, the lithium manganese iron phosphate precursor is obtained after solid-liquid separation, washing and drying.

[0058] In step C, the carbon source can be selected from glucose. Specifically, the lithium manganese iron phosphate precursor and the carbon source can be uniformly mixed, and then an appropriate amount of deionized water is added as a dispersant, and then ball milling is performed, the ball-to-material ratio of the ball milling is (4-5): 1, the rotation speed is 1200r / min-1500r / min, the time is 20h-25h, and then the ball-milled material is spray-dried, the pump speed is 8mL / min-12mL / min, and the outlet drying temperature is 180°C-220°C to form a powder, and the surface of the powder is coated with glucose.

[0059] In step D, the high temperature sintering treatment (hereinafter referred to as the first sintering) can be performed in a vacuum atmosphere sintering furnace, and the protective atmosphere is nitrogen. The glucose coated on the surface of the powder is carbonized to form conductive carbon, which is beneficial to improve the conductivity of the positive electrode material.

[0060] In an optional embodiment, the mass ratio of porous hollow carbon microspheres to reaction raw materials is (10-15):100. For example, the mass ratio of porous hollow carbon microspheres to reaction raw materials is 10:100, 12:100 or 15:100. In the present application, the porous hollow carbon microspheres mainly play the role of pore formation. When the proportion of porous hollow carbon microspheres is too small, the proportion of pore formation area in the particles of the positive electrode material is reduced, resulting in reduced wettability of the positive electrode material to the electrolyte; when the proportion of porous hollow carbon microspheres is too large, the overall structure of the positive electrode material particles will be destroyed, and the positive electrode material particles will be at risk of breaking. By regulating the mass ratio of porous hollow carbon microspheres to reaction raw materials within the above range, it is beneficial to form the first pores and the second pores of the present application, so that the positive electrode material has both good electrolyte wettability and sufficient mechanical strength.

[0061] In an optional embodiment, the mass ratio of the lithium iron manganese phosphate precursor to the carbon source is (93-97): (3-7). For example, the mass ratio of the lithium iron manganese phosphate precursor to the carbon source is 93:7, 95:5 or 97:3. When the carbon source accounts for too little, the coating effect on the positive electrode material particles is not good, the conductivity is poor, and it is not conducive to the performance of the electrical properties of the positive electrode material; when the carbon source accounts for too much, it will inhibit the growth of the positive electrode particles, increase the difficulty of regulating the size of the positive electrode particles, and the relative content of the active material becomes less, resulting in a decrease in the overall capacity of the positive electrode material. By regulating the mass ratio of the lithium iron manganese phosphate precursor to the carbon source within the above range, it is beneficial to both the performance of the electrical properties of the positive electrode material and the improvement of the overall capacity of the positive electrode material.

[0062] In an optional embodiment, the porous hollow carbon microspheres are obtained by the following steps:

[0063] Step a, forming a carbon microsphere precursor by spray drying a sucrose solution;

[0064] Step b: subjecting the carbon microsphere precursor to a low-temperature sintering treatment at a temperature of 400° C. to 450° C. to obtain porous hollow carbon microspheres.

[0065] In step a, the concentration of the sucrose solution is 12 mol / L to 17 mol / L; the outlet temperature of the spray drying is 145° C. to 155° C., which is used to form a powdered carbon microsphere precursor after the sucrose solution is initially dried;

[0066] In step b, the role of the low-temperature sintering treatment (referred to as the second sintering) is to shrink the carbon microsphere precursor under heat, thereby forming a porous structure inside it; the time of the low-temperature sintering treatment is 3h to 5h. The Dv50 of the carbon microsphere precursor of the present application is 150nm to 200nm, which is conducive to the formation of a positive electrode material with a particle size range of the present application.

[0067] The present application has no particular restrictions on the method of regulating the proportion of the area of ​​the second hole in the total area of ​​the cross section (i.e., the A value), as long as the purpose of the present application can be achieved. Exemplarily, the A value generally increases with the increase in the amount of porous hollow carbon microspheres added and increases with the increase in the high-temperature sintering temperature. Based on this, the size of the A value can be regulated by regulating the amount of porous hollow carbon microspheres added and / or the warm sintering temperature during the preparation of the positive electrode material.

[0068] The present application provides a method for preparing a positive electrode material. The porous hollow carbon microspheres are easy to agglomerate in the liquid phase solution due to their small particle size (about 150nm to 200nm), and are enriched in the subsequent synthesis of lithium manganese iron phosphate precursors, which promotes the occurrence of "radial" and "arc-shaped" cracking due to uneven shrinkage stress during high-temperature sintering, and prepares a positive electrode material having the first pore and second pore structure of the present application; and has the advantages of a wide source of raw materials and a simple preparation process, and improves the capacity performance and rate performance of the positive electrode material. When the positive electrode sheet with the positive electrode material of the present application is used in a lithium-ion battery, the rate performance and cycle performance of the lithium-ion battery can be improved.

[0069] The present application also provides a battery, comprising the positive electrode sheet described in any of the above embodiments.

[0070] In the present application, the positive electrode material layer can be arranged on one surface in the thickness direction of the positive electrode current collector, or on two surfaces in the thickness direction of the positive electrode current collector. In the present application, the positive electrode material layer is arranged on the surface of the positive electrode current collector, that is, the positive electrode material layer can be arranged in a partial area of ​​one surface of the positive electrode current collector, or in the entire area of ​​one surface of the positive electrode current collector. In the present application, there is no special restriction on the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, it can include but is not limited to aluminum foil, aluminum alloy foil or composite current collector. In the present application, there is no special restriction on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the positive electrode material layer of the present application can be 8μm to 15μm.

[0071] The lithium-ion battery of the present application also includes a negative electrode sheet. The present application has no special restrictions on the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the negative electrode sheet generally includes a negative electrode collector and a negative electrode material layer. The negative electrode material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode collector. In the present application, the negative electrode material layer is arranged on the surface of the negative electrode collector, that is, the negative electrode material layer can be arranged in a partial area of ​​one surface of the negative electrode collector, or in the entire area of ​​one surface of the negative electrode collector. The present application has no special restrictions on the negative electrode collector, as long as the purpose of the present application can be achieved. For example, it can include but is not limited to copper foil, copper alloy foil, nickel foil or composite current collector. In the present application, there is no special restriction on the thickness of the negative electrode collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the negative electrode material layer of the present application can be 70μm to 200μm.

[0072] In the present application, the negative electrode material layer includes a negative electrode material, wherein the negative electrode material is not particularly limited as long as the purpose of the present application can be achieved. For example, it may include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon, hard carbon, silicon, and silicon carbon.

[0073] In the present application, the negative electrode material layer may further include a negative electrode binder. The present application has no particular restrictions on the negative electrode binder, as long as it can achieve the purpose of the present application, for example, it may include but is not limited to at least one of acrylate, polyamide, polyimide, polyamideimide, polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, and potassium carboxymethyl cellulose.

[0074] The lithium-ion battery of the present application also includes a diaphragm. The present application has no particular restrictions on the diaphragm, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.

[0075] The battery of the present application also includes an electrolyte. The present application has no particular restrictions on the electrolyte, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP), propyl propionate (PP), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) or fluoroethylene carbonate (FEC) is mixed in a certain mass ratio or volume ratio to obtain a non-aqueous organic solvent, and then a lithium salt is added to dissolve and mix evenly. The present application has no restrictions on the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate. The present application has no particular limitation on the concentration of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, the concentration of the lithium salt is 1.0 mol / L to 2.0 mol / L.

[0076] The battery of the present application also includes a shell, and the present application has no particular limitation on the shell, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the shell may include an aluminum-plastic film.

[0077] The present application does not particularly limit the preparation method of the battery, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain a bare cell with a wound structure, placing the bare cell in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a battery.

[0078] The present application also provides an energy storage device, including a housing and at least one battery in any of the above embodiments, wherein the battery is contained in the housing. The energy storage device having the battery has excellent performance, which is beneficial to the use of the energy storage device. By containing the battery in the housing, the fixation and protection of the battery can be increased, thereby improving the service life of the energy storage device. It is understandable that the energy storage device may have one or more batteries, and when the energy storage device contains multiple batteries, the multiple batteries may be connected in at least one of parallel and series connection.

[0079] The present application also provides an electrical device, including the energy storage device in the above-mentioned implementation scheme, which is conducive to improving the product competitiveness and performance of the electrical device. In an optional implementation scheme, the electrical device includes an electrical device body, and the energy storage device is used to supply power to the electrical device body. In an optional implementation scheme, the electrical device body includes a positive electrode of the device and a negative electrode of the device, the positive electrode plate of the battery in the energy storage device is used to electrically connect to the positive electrode of the device body of the electrical device, and the negative electrode plate of the battery in the energy storage device is used to electrically connect to the negative electrode of the device body of the electrical device, so as to supply power to the electrical device.

[0080] The electrical equipment of the present application may include but is not limited to: containers, household energy storage systems, battery vehicles, electric vehicles, ships, spacecraft, electric toys and electric tools, etc., wherein spacecrafts include airplanes, rockets, space shuttles and spacecrafts, etc., electric toys include fixed or mobile electric toys, such as electric car toys, electric ship toys and electric airplane toys, etc., and electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.

[0081] See also Figure 3 , Figure 3 This is a schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application, and the present application Figure 3The implementation plan is described using the household energy storage scenario in user-side energy storage as an example, but the energy storage device of the present application is not limited to the household energy storage scenario.

[0082] The present application provides a household energy storage system, which includes an energy conversion device 2 (photovoltaic panel), a first user load 3 (street lamp), a second user load 4 (such as air conditioner and other household appliances), and an energy storage device 1. The energy storage device 1 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electrical energy during the period of low electricity prices. The energy storage device 1 is used to store the electrical energy and supply it to street lamps and household appliances for use during the peak electricity prices, or to supply power when the power grid is out of power / power outage.

[0083] See also Figure 4 , Figure 4 This is a schematic diagram of the structure of an energy storage system 400 according to an implementation scheme of the present application, and the present application Figure 4 The implementation plan is described using the shared energy storage scenario on the generation / distribution side as an example, and the energy storage device 1 of the present application is not limited to the energy storage scenario on the generation / distribution side.

[0084] The present application provides an energy storage system 400, which includes: a high-voltage cable 410, a first electric energy conversion device 420, a second electric energy conversion device 430 and an energy storage device 1 provided in the present application. In the case of power generation, the first electric energy conversion device 420 and the second electric energy conversion device 430 are used to convert other forms of energy into electric energy, which are connected to the high-voltage cable 410 and supplied to the power distribution network for use. When the power load is low and the first electric energy conversion device 420 and the second electric energy conversion device 430 generate excess power, the excess power is stored in the energy storage device 1, thereby reducing the wind and solar power abandonment rates and improving the problem of new energy power generation and consumption. When the power load is high, the power grid issues an instruction to transmit the power stored in the energy storage device 1 in conjunction with the high-voltage cable 410 in a grid-connected mode to the power consumption side, thereby providing peak shaving, frequency regulation, standby and other services for the power grid operation, giving full play to the peak shaving role of the power grid, promoting peak shaving and valley filling of the power grid, and alleviating the power supply pressure of the power grid.

[0085] Optionally, the first electric energy conversion device 420 and the second electric energy conversion device 430 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.

[0086] The number of energy storage devices 1 can be multiple, and multiple energy storage devices 1 are connected in series or in parallel. Multiple energy storage devices 1 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 1 to accommodate the energy storage device 1.

[0087] Optionally, the energy storage device 1 may include but is not limited to a battery module, a battery pack, a battery system, etc. Among them, the battery module may be a battery module formed by connecting multiple batteries of the present application in series / parallel, the battery pack may include multiple batteries of the present application, and the battery system may be a charging and discharging system including the battery or battery pack of the present application.

[0088] The actual application form of the energy storage device 1 provided in the embodiment of the present application may be, but is not limited to, the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 1. The embodiment of the present application only takes the energy storage device 1 as a multi-core battery as an example for explanation. When the energy storage device 1 is a single battery, the energy storage device 1 may be at least one of a cylindrical battery, a square battery, and the like.

[0089] Example

[0090] Hereinafter, the embodiments of the present application will be described in more detail with reference to preparation examples, examples and comparative examples. Various tests and evaluations were performed according to the following methods.

[0091] Example 1

[0092] <Preparation of positive electrode sheet>

[0093] <Preparation of positive electrode material>

[0094] A sucrose solution with a concentration of 15 mol / L was prepared, and a carbon microsphere precursor was formed by spray drying, and the outlet temperature of the spray drying was 150°C; the carbon microsphere precursor was subjected to a low-temperature sintering treatment at a temperature of 450°C for 4 hours to obtain porous hollow carbon microspheres, and the Dv50 of the porous hollow carbon microspheres was 150 nm; according to LiMn 0.5 Fe 0.49 Mg 0.01PO4, iron source ferrous oxalate, manganese source manganese dioxide, phosphoric acid, phosphorus source, lithium source lithium carbonate and magnesium source magnesium oxide are weighed as reaction raw materials in the required stoichiometric ratio, and pure water is added to form a metal salt solution; the prepared porous hollow carbon microspheres are then mixed with the reaction raw materials in the metal salt solution in a mass ratio of 10:100 to obtain a mixed solution; the mixed solution, sodium hydroxide solution (1 mol / L) and ammonia solution (1 mol / L) are then mixed and placed in a reactor, and stirred continuously to maintain the pH value of the reaction system at 10, and a precipitation reaction is carried out at a reaction temperature of 150°C and a reaction time of 10 h. After solid-liquid separation, washing and drying, manganese phosphate is obtained. Iron lithium precursor; the prepared manganese iron phosphate lithium precursor is mixed with carbon source glucose in a mass ratio of 95:5, and then an appropriate amount of deionized water is added as a dispersant, and then ball milling is performed, the ball-to-material ratio of the ball milling is 4:1, the rotation speed is 1300r / min, and the time is 20h, and then the ball-milled material is spray-dried, the pump speed is 10mL / min, and the outlet drying temperature is 200℃ to form a powder; the obtained powder is placed in a vacuum atmosphere sintering furnace for high-temperature sintering treatment, the protective atmosphere is nitrogen, the sintering temperature is 650℃, and the sintering time is 10h, and then the positive electrode material is obtained after grinding and crushing, and the Dv50 of the positive electrode material is 5μm.

[0095] <Preparation of positive electrode material layer>

[0096] The positive electrode material, conductive carbon black (Super-P), and binder PVDF are mixed in a mass ratio of 95:2:3, and then N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 50wt%, and stirred evenly. Then, the positive electrode slurry is evenly coated on one surface of a positive electrode collector with a thickness of 10μm, dried at 85°C, and then the above steps are repeated on the other surface of the positive electrode sheet. After rolling, a positive electrode sheet coated with a positive electrode material layer on both sides is obtained, and the single-side thickness of the positive electrode material layer is 100μm.

[0097] <Preparation of negative electrode sheet>

[0098] The negative electrode materials artificial graphite, conductive carbon black Super-P and sodium carboxymethyl cellulose (CMC-Na) were mixed in a mass ratio of 95:2.5:2.5, deionized water was added, and a negative electrode slurry with a solid content of 60wt% was prepared, and stirred evenly. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, dried at 85℃, and then the above steps were repeated on the other surface of the negative electrode sheet. After rolling, a negative electrode sheet with a negative electrode material layer coated on both sides was obtained, and the single-side thickness of the negative electrode material layer was 70μm.

[0099] <Preparation of Electrolyte>

[0100] Ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1, dissolved and fully stirred, and then placed in an environment of 5°C or less for 12 hours, and then lithium salt LiPF6 is added and mixed evenly to obtain an electrolyte. The molar concentration of LiPF6 in the electrolyte is 1 mol / L.

[0101] <Preparation of Separator>

[0102] A polyethylene (PE) porous polymer film with a thickness of 16 μm was used as the separator.

[0103] <Assembly of lithium-ion batteries>

[0104] The prepared positive electrode sheet and negative electrode sheet are respectively placed in a press for pressing, and then a puncher is used to cut out a circular positive electrode sheet with a diameter of 15 mm and a circular negative electrode sheet with a diameter of 18 mm respectively; then the circular positive electrode sheet, the diaphragm and the circular negative electrode sheet are stacked in order, so that the diaphragm is placed between the circular positive electrode sheet and the circular negative electrode sheet to play an isolating role, and then the prepared electrolyte is injected to assemble into a lithium-ion battery.

[0105] Embodiment 2 to Embodiment 3

[0106] Except that in <Preparation of Positive Electrode Material>, the mass ratio of porous hollow carbon microspheres to reaction raw materials is adjusted according to Table 1 to control the value of A, the rest is the same as Example 1.

[0107] Embodiment 4 to Embodiment 5

[0108] Except that in <Preparation of Positive Electrode Material>, the temperature of high temperature sintering is adjusted according to Table 1 to control the value of A, the rest is the same as Example 1.

[0109] Embodiment 6 to Embodiment 13

[0110] Except that in <Preparation of Positive Electrode Material>, the amount of each raw material added and the type of doping element are adjusted according to the stoichiometric ratio in Table 2, the rest is the same as Example 1.

[0111] Comparative Example 1 to Comparative Example 2

[0112] Except that in <Preparation of Positive Electrode Material>, the mass ratio of porous hollow carbon microspheres to reaction raw materials is adjusted according to Table 1 to control the value of A, the rest is the same as Example 1.

[0113] Comparative Example 3 to Comparative Example 4

[0114] Except that in <Preparation of Positive Electrode Material>, the temperature of high temperature sintering is adjusted according to Table 1 to control the value of A, the rest is the same as Example 1.

[0115] Comparative Example 5 to Comparative Example 7

[0116] Except that in <Preparation of Positive Electrode Material>, the amount of each raw material added and the type of doping element are adjusted according to the stoichiometric ratio in Table 2, the rest is the same as Example 1.

[0117] Table 1 Preparation parameters of Examples 1 to 5 and Comparative Examples 1 to 4

[0118]

[0119] Table 2 Preparation parameters of Example 1, Example 6 to Example 13, Comparative Example 5 to Comparative Example 7

[0120]

[0121] Test methods and equipment:

[0122] Material particle size distribution test:

[0123] The particle size distribution of the positive electrode material was measured using a laser diffraction particle size distribution measuring instrument (model: Malvern Mastersizer 3000) according to the particle size distribution laser diffraction method (GB / T19077-2016), thereby measuring the Dv50 of the positive electrode material.

[0124] Measurement of the second hole area ratio of positive electrode material particles:

[0125] The positive electrode sheet was cut using a focused ion beam, and then a scanning electron microscope was used to observe the cross-sectional distribution of the positive electrode material particles in the positive electrode material layer in the positive electrode sheet, with a shooting magnification of 5K. ImageJ software was used to measure the sum of the areas of the arc-shaped holes (i.e., the second holes) of 100 positive electrode material particles, recorded as S1, and the total area of ​​100 positive electrode material particles, recorded as S 总 , then the value of the second hole area ratio A is [(S1 / S 总 ) / 100]×100%.

[0126] Second hole length test:

[0127] The positive electrode sheet was cut using a focused ion beam, and then a scanning electron microscope was used to observe the cross-sectional distribution of the positive electrode material particles in the positive electrode material layer in the positive electrode sheet, with a shooting magnification of 5 K. The ImageJ software was used to measure the sum of the lengths of the arc-shaped holes (i.e., the second holes) of 100 positive electrode material particles, and then the average value was taken.

[0128] XRD test:

[0129] The positive electrode material was tested using an X-ray diffractometer (model: D500 Siemens), the test target was a copper target (λ=0.154 nm), the scanning speed was 3° / min, the scanning angle was 10-90°, and the radiation source was a CuKα radiation source.

[0130] Rate performance test:

[0131] The test temperature is 25°C. The lithium-ion battery is charged to 4.3V at a rate of 0.5C, and then discharged to 2.5V at a rate of 0.5C. This is recorded as the 0.5C discharge capacity. Then it is charged to 4.3V at a rate of 1C, and then discharged to 2.5V at a rate of 1C. This is recorded as the 1C discharge capacity in mAh / g.

[0132] Cycle performance test:

[0133] The test temperature is 25°C. The lithium-ion battery is charged to 4.3V at 1C constant current, and then discharged to 2.5V at 1C after standing for 10 minutes. The capacity obtained in this step is the initial discharge capacity C0. A 1C charge / 1C discharge cycle test is performed for 200 cycles, and the discharge capacity at the 200th cycle is recorded. Cycle capacity retention rate = (discharge capacity at the 200th cycle / initial discharge capacity C0) × 100%.

[0134] Table 3 Performance data of each embodiment and comparative example

[0135]

[0136]

[0137] Combining Table 1 and Table 3, it can be seen from Examples 1 to 5 and Comparative Examples 1 to 4 that the 0.5C discharge capacity, 1C discharge capacity and capacity retention rate of Comparative Example 1 are all low. This may be due to the fact that the amount of porous hollow carbon microspheres added in Comparative Example 1 is too small, resulting in a too low A value, that is, the area of ​​the arc-shaped second pores accounts for a small proportion, and Li +The migration distance is large, which is not conducive to the capacity, and thus is not conducive to the capacity performance and capacity retention rate of the positive electrode material; the 0.5C discharge capacity and 1C discharge capacity of comparative example 2 are low, and the capacity retention rate is low. This may be due to the excessive addition of porous hollow carbon microspheres in comparative example 2. During high-temperature sintering, the particles are subjected to more uneven stress concentration, resulting in an excessive proportion of arc-shaped area, which will cause the particles to crack and break easily, destroy the overall structure, and cause the electrochemical performance of the positive electrode material to decline; the 0.5C discharge capacity, 1C discharge capacity and capacity retention rate of comparative example 3 are all low, which may be due to the sintering temperature of comparative example 3 being too low, which is not conducive to the formation of the arc-shaped second pores, resulting in an excessively small proportion of arc-shaped area, causing the electrochemical performance of the positive electrode material to decline; the 0.5C discharge capacity, 1C discharge capacity and capacity retention rate of comparative example 4 are all low, which may be due to the sintering temperature of comparative example 4 being too high, resulting in the expansion of the arc-shaped structure, which in turn causes the arc-shaped area to account for a large proportion, which will cause the particles to crack and break easily, destroy the overall structure, and cause the electrochemical performance of the positive electrode material to decline. The lithium-ion battery of the present application exhibits good 0.5C discharge capacity, 1C discharge capacity and capacity retention rate, and improves the capacity performance and rate performance of the positive electrode material.

[0138] The content of each element in the positive electrode material will usually also have an impact on the performance of the positive electrode sheet. In combination with Table 2 and Table 3, it can be seen from Example 1, Example 6 to Example 13, and Comparative Example 5 to Comparative Example 7 that the 0.5C discharge capacity, 1C discharge capacity and capacity retention rate of Comparative Example 5 are all low. This may be due to the excessively high content of the Mn element in Comparative Example 5, which leads to a decrease in the electrochemical performance of the positive electrode material; the 0.5C discharge capacity, 1C discharge capacity and capacity retention rate of Comparative Example 6 and Comparative Example 7 are all low. This may be due to the excessively high content of the M element as a doping element in Comparative Example 6 and Comparative Example 7, which causes the positive electrode material to produce heterogeneous compounds and reduce the capacity performance. On the basis of the positive electrode material having the structural characteristics of the present application, by regulating the content of each element in the positive electrode material and the type of doping element, it is beneficial to obtain a lithium-ion battery with excellent capacity performance and cycle performance.

[0139] Figure 1 The SEM image of the cross section of the positive electrode material obtained in Example 1 is shown in FIG. Figure 1 It can be seen that the cross section of the positive electrode material particle has multiple radial ion transmission channels, and each ion transmission channel is composed of multiple first holes distributed along the center to the surface of the cross section; and the central area of ​​the cross section also has an arc-shaped second hole.

[0140] Figure 5 The XRD spectrum of the positive electrode material obtained in Example 1 has a first diffraction characteristic peak (110) and a second diffraction characteristic peak (131), and the peak intensity of the first diffraction characteristic peak is 1 110, the peak intensity of the second diffraction characteristic peak is I 131 , I 131 / I 110 The XRD test of the positive electrode materials prepared in other embodiments of the present invention also showed similar I 131 / I 110 ratio.

[0141] The above is a detailed introduction to a positive electrode sheet, a method for preparing a positive electrode material, a battery and an energy storage device disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core inventions of the embodiments of the present application. At the same time, for those skilled in the art, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector, at least one side of which has a positive electrode material layer, and the positive electrode material layer comprises a positive electrode material, wherein: The positive electrode material has the chemical formula LiMn x Fe 1-x-y M y PO4, 0.5≤x≤0.7, 0.01≤y≤0.04, M element is selected from at least one of Mg and Ti; The cross section of the particles of the positive electrode material has radially distributed first holes, and the central area of ​​the cross section also has arc-shaped second holes.

2. The positive electrode sheet according to claim 1, characterized in that: In the cross section of the positive electrode material particle, the area of ​​the second pore accounts for A in the total area of ​​the cross section, and 8%≤A≤21%.

3. The positive electrode sheet according to claim 1, characterized in that: The length of the second hole is L, where L≥5 μm.

4. The positive electrode sheet according to claim 1, characterized in that: The cross section of the positive electrode material particle has a plurality of radial ion transmission channels, and each of the ion transmission channels is formed by a plurality of the first holes distributed along the center to the surface of the cross section.

5. The positive electrode sheet according to claim 1, characterized in that: The Dv50 of the positive electrode material is 5 μm to 8 μm.

6. The positive electrode sheet according to claim 1, characterized in that: The XRD spectrum of the positive electrode material includes a first diffraction characteristic peak (110) and a second diffraction characteristic peak (131), wherein the peak intensity of the first diffraction characteristic peak is 1 110 , the peak intensity of the second diffraction characteristic peak is I 131 , 1.445≤I 131 / I 110 ≤1.

455.

7. The positive electrode sheet according to claim 1, characterized in that: The button cell containing the positive electrode sheet has a 0.5C discharge capacity of not less than 140 mAh / g, a 1C discharge capacity of not less than 130 mAh / g, and a 200-cycle capacity retention rate of not less than 84%.

8. A method for preparing a positive electrode material, characterized in that: The method comprises the following steps: According to LiMn x Fe 1-x-y M y Iron source, manganese source, phosphorus source, lithium source and M element source are weighed as reaction raw materials in the stoichiometric ratio required by PO4, and water is added and mixed to prepare a metal salt solution, wherein 0.5≤x≤0.7, 0.01≤y≤0.04, and M element is selected from at least one of Mg and Ti; After mixing the metal salt solution, the porous hollow carbon microspheres, the precipitant solution and the complexing agent solution, the pH value of the reaction system is maintained to be greater than or equal to 10, and a precipitation reaction is performed to obtain a lithium manganese iron phosphate precursor; The obtained lithium manganese iron phosphate precursor is mixed with a carbon source and then spray-dried to form a powder; The obtained powder is subjected to a high temperature sintering treatment at a temperature of 650° C. to 750° C. to obtain a positive electrode material.

9. The preparation method according to claim 8, characterized in that: The mass ratio of the porous hollow carbon microspheres to the reaction raw materials is (10-15):

100.

10. The preparation method according to claim 8, characterized in that: The mass ratio of the lithium manganese iron phosphate precursor to the carbon source is (93-97): (3-7).

11. The preparation method according to claim 8, characterized in that: The porous hollow carbon microspheres are obtained by the following steps: The sucrose solution is spray-dried to form a carbon microsphere precursor; The carbon microsphere precursor is subjected to a low-temperature sintering treatment at a temperature of 400° C. to 450° C. to obtain the porous hollow carbon microspheres.

12. A battery, characterized in that: The invention comprises the positive electrode sheet as described in any one of claims 1 to 7.

13. An energy storage device, characterized in that: The invention comprises a casing and at least one battery according to claim 12, wherein the battery is accommodated in the casing.

14. An electrical device, characterized in that: It includes the energy storage device as described in claim 13, and the energy storage device supplies power to the electrical equipment.